Managing the Miombo Woodlands of Southern Africa : Policies, Incentives and Options for the Rural Poor, Volume 2. Technical Annexes - World Bank (Washington, DC, 2014)
Miombo woodlands stretch across Southern Africa in a belt from Angola and the Democratic Republic of Congo (DRC) in the west to Mozambique in the east. The miombo region covers an area of around 2.4 million km. In some areas, miombo has been highly degraded as a result of human use (southern Malawi and parts of Zimbabwe), while in others, it remains relatively intact (such as in parts of northern Mozambique, and in isolated areas of Angola and the DRC). From a conventional forester's perspective, miombo is fundamentally uninteresting. It supports relatively few good commercial timber species. The management of commercial species has been problematic. The best areas were logged over long ago. Except in a few areas, remaining commercially viable stocks are relatively small and difficult to access. Public forestry institutions have, for the most part, failed to put in place effective management systems for forests, preferring instead to limit their role to regulation and revenue collection, rather than to management per se. The objectives of this paper are threefold, and the paper is structured around these objectives. First, in section two, the paper describes some of opportunities for improving the use and management of miombo woodlands. Second, in section three, outline some of the barriers which are preventing households, communities, and countries from adopting better and more sustainable woodland management practices. In section four, by exploring some of the policy opportunities for removing these barriers, with the objective of strengthening miombo's contribution to reducing risk and vulnerability of poor rural households through sustainable forest management.